2014
DOI: 10.3758/s13423-013-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adaptation to change in implicit contextual learning

Abstract: The visual world consists of spatial regularities that are acquired through experience in order to guide attentional orienting. For instance, in visual search, detection of a target is faster when a layout of nontarget items is encountered repeatedly, suggesting that learned contextual associations can guide attention (contextual cuing). However, scene layouts sometimes change, requiring observers to adapt previous memory representations. Here, we investigated the long-term dynamics of contextual adaptation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 20 publications
10
54
1
Order By: Relevance
“…The purpose of Experiment 1 was to show, in the first instance, that with our stimuli we can actually replicate previous findings showing a general lack of adaptation in contextual cueing to relocated targets (e.g., Zellin et al, 2014).…”
Section: Experiments 1 (Baseline)supporting
confidence: 66%
See 2 more Smart Citations
“…The purpose of Experiment 1 was to show, in the first instance, that with our stimuli we can actually replicate previous findings showing a general lack of adaptation in contextual cueing to relocated targets (e.g., Zellin et al, 2014).…”
Section: Experiments 1 (Baseline)supporting
confidence: 66%
“…Further, they appear to be at odds with Zellin et al (2014), who found adaptation of contextual cueing only after massive amounts of training with the 'relocated' displays. However, Zellin et al did not control for local item density -a manipulation that was central to the current experiments.…”
Section: Lack Of Adaptation Of Contextual Cueing Revisitedmentioning
confidence: 86%
See 1 more Smart Citation
“…19,No. 9 delays lasting weeks [21][22][23] and strongly resists retroactive interference [22,23]. CC is not confined to humans because similar CC effects have been reported in baboons [21] and pigeons [24].…”
Section: Reviewmentioning
confidence: 77%
“…Consequently, a search task that includes much fewer trials within each block triggers larger CC effects [112]. Congruently, the acquisition of a new set of old displays is strongly impeded by proactive interference, and requires intensive training or a nap to take place [15,23]. Interestingly, sleep has been shown to reduce proactive inference only for the contexts that are not available in recognition task [15].…”
Section: Flexibility Versus Hyperspecificitymentioning
confidence: 99%